Women in Nineteenth-Century Russia Lives and Culture - Tosi, Alessandra; Rosslyn, Wendy (Open Book Publishers, 2012)
Russian women of the nineteenth century are often thought of in their literary incarnations as the heroines of novels such as Anna Karenina and War and Peace. But their real counterparts are now becoming better understood as active contributors to Russia's varied cultural landscape. This collection of essays examines the lives of women across Russia - from wealthy noblewomen in St Petersburg to desperately poor peasants in Siberia - discussing their interaction with the church and the law, and their rich contribution to music, art, literature and theatre. It shows how women struggled for greater autonomy and, both individually and collectively, developed a dynamic but often overlooked presence in Russia's culture and society during the long nineteenth century (1800-1917). Women in Nineteenth-Century Russia provides invaluable reading for anyone interested in Russian history, nineteenth-century culture and gender studies.